2018
DOI: 10.1186/s12887-018-1059-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated central venous pressure is associated with increased mortality in pediatric septic shock patients

Abstract: BackgroundCentral venous pressure (CVP) is an important factor affecting capillary blood flow, and it is associated with poor outcomes in adult septic shock patients. However, whether a similar association exists in pediatric patients remains unclear.MethodsWe retrospectively analyzed data from patients admitted to our pediatric intensive care unit (PICU) between February 2009 and July 2015. Patients were divided into two groups—survivors and nonsurvivors—according to 28-day mortality. The associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…This figure is relatively high when compared with the 10.5 and 24.9% mortality rates reported by the American and multinational studies of Gorgis et al ( 27 ) and Fitzgerald et al ( 28 ), but it is fairly lower than the 50.0% mortality rate reported by the study of Nyirasafari et al ( 29 ) from Rwanda ( 27 29 ). However, our mortality rate accords with the Chinese figure of 29.6% ( 30 ). The current study found that PI and RI values were higher in the non-survivor group in comparison with the survivor one.…”
Section: Discussionsupporting
confidence: 87%
“…This figure is relatively high when compared with the 10.5 and 24.9% mortality rates reported by the American and multinational studies of Gorgis et al ( 27 ) and Fitzgerald et al ( 28 ), but it is fairly lower than the 50.0% mortality rate reported by the study of Nyirasafari et al ( 29 ) from Rwanda ( 27 29 ). However, our mortality rate accords with the Chinese figure of 29.6% ( 30 ). The current study found that PI and RI values were higher in the non-survivor group in comparison with the survivor one.…”
Section: Discussionsupporting
confidence: 87%
“…Studies in adults show that delayed graft function in kidney transplantation is related to postoperative ABP but not to CVP . Moreover, higher CVP levels and fluid overload are associated with higher risks of acute kidney injury, renal replacement therapy, and mortality in critically ill children . In a retrospective analysis, postoperative renal replacement therapy was related to high volumes of intra‐operative fluid administration related to body weight and a higher donor‐recipient weight ratio .…”
Section: Discussionmentioning
confidence: 98%
“…21 Moreover, higher CVP levels and fluid overload are associated with higher risks of acute kidney injury, renal replacement therapy, and mortality in critically ill children. 22,23 In a retrospective analysis, postoperative renal replacement therapy was related to high volumes of intra-operative fluid administration related to body weight and a higher donor-recipient weight ratio. 5 This supports the idea that CVP-guided fluid administration may lead to tissue edema, especially in small children.…”
Section: Pressure-guidedmentioning
confidence: 99%
“…Care should be taken when interpreting central venous pressure, as central venous pressure is related to both intravascular volume and right and left ventricular compliance. Further, children in septic shock with elevated central venous pressure frequently have diastolic dysfunction and left heart strain, which are associated with increased mortality [18][19][20]. Prediction of fluid responsiveness using other hemodynamic variables is an area of active interest, with some data supporting the use of aortic flow velocity and arterial pulse pressure variability with respiration [21,22].…”
Section: Strategies To Improve Oxygen Deliverymentioning
confidence: 99%